Ecological Assessment and Local Knowledge of the Invasive Lionfish (Pterois miles) in the Coastal Waters of Derna, Eastern Libya (مجلة الفاروق للعلوم, 2026)
The common lionfish, scientifically known as Pterois miles (Bennett, 1828), is a relatively new addition to the Mediterranean Sea, brought into the region through the Lessepsian migration. This species poses a significant threat to the marine ecosystems in this area.The native habitat of the lionfish, also referred to as the devil firefish, is the Indo-Pacific biogeographic realm, encompassing regions from the Red Sea to South Africa and extending eastward to Indonesia (Fricke, 1999; Froese and Pauly, 2019). Initially, there was only a solitary record of this species in the Mediterranean Sea in 1991, suggesting a failed establishment of a viable population (Golani and Sonin, 1992). However, a resurgence occurred two decades later in 2012, with new lionfish specimens likely introduced from the Red Sea (Bariche et al., 2013, 2015, 2017).In the following years, as time progressed, the common lionfish began to proliferate and expand its range in the Mediterranean Sea, swiftly reaching locations as distant as Tunisia and Sicily within a relatively short period (Azzurro et al., 2017; Al Mabruk and Rizgalla, 2019). Notably, despite the country's proximity to the Suez Canal and a recent sighting in Libya, this species has not yet been observed in Egyptian Mediterranean waters, with the most recent documented record from Egypt (Al Mabruk et al., 2020).The population density of lionfish has increased dramatically in Cyprus since the first sighting in late 2012; by 2018 aggregations of up to 70 lionfish were found on rocky grounds with complex reefs and artificial reefs in depths of 0–50 m. Lionfish in Cyprus become mature within a year, and adults are capable of spawning year-round, with peak spawning in summer when the sea-surface temperature reaches 28.4°C. The Cypriot lionfish grow faster and bigger than in their native range, and females are more common than males. Lionfish are generalist predators in these waters, as also found in their native range, consuming a range of teleost and crustacean prey, some of which are of high economic value (e.g., Spicarasmaris and Sparisomacretense).or have an important role in local trophic webs (e.g., Chromischromis). Overall, the reproductive patterns, the presence of juveniles and adults throughout the year, the rapid growth rates and the generalist diet indicate that lionfish are thriving and are now already well established in the region and could potentially become the serious nuisance that they are in their temperate and tropical western Atlantic–invasive range.Bioinvasions threaten marine environments as they can harm native species across all trophic levels (Anton et al., 2019). Anthropogenic corridors are major pathways for introductions of marine species in the Mediterranean Sea (Galil et al., 2017; Katsanevakis et al., 2013),The primary goal of this study is to provide an initial assessment of the feeding behavior of lionfish (Pterois miles) in the coastal waters of Derna and its neighboring areas. Additionally, the study aims to gather local knowledge from divers and fishermen regarding lionfish. The information collected from this study will lay the groundwork for a comprehensive, long-term research project.